International trade restrictions and their impact on international relations: dispute settlement within the World Trade Organization - Paeglīte, Elīna (Riga Graduate School of Law, 2020)
In a world where trade relations between states are of tremendous importance, it is inevitable to avoid conflict. For the purposes of minimizing the risk of differences coming between various jurisdictions, the World Trade Organization has established principles, rules and mechanisms which seek to create a uniform set of rules that Members are bound by. Nevertheless, even though Members have undertaken to comply with the rules outlined in several Agreements, they still tend to violate them due to reasons such as conflicting internal laws, national security issues or dissatisfaction with the policies of their trading partners. The dispute settlement procedure and the recommendations issued by the WTO are of a binding nature; however, it has been observed that states do not always comply, which further leads to the imposition of sanctions. The study suggests that the legal outcomes of cases brought to the Dispute Settlement Body of the WTO vary, as do their effects of international relations since issues related to trade mostly arise out of political differences. Nevertheless, over time, states tend to solve their disputes due to reasons of co-dependency and collateral damage.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Dispute settlement; World Trade Organization